(untitled) (CIPEEX, 2024)
HOME CARE (HC) IS A FORM OF HEALTH CARE PROVIDED IN THE PATIENT’S HOME AND CHARACTERIZED BY A SERIES OF HEALTH PROMOTION, DISEASE PREVENTION, TREATMENT AND REHABILITATION ACTIONS THAT GUARANTEE CONTINUITY OF CARE AND ARE INTEGRATED INTO THE HEALTH CARE NETWORK. THE €ŒMELHOR EM CASA€ (BETTER AT HOME) PROGRAM WAS CREATED TO ASSIST PATIENTS WITH HEALTH PROBLEMS WHO HAVE DIFFICULTY OR ARE PHYSICALLY UNABLE TO GET TO MEDICAL CENTERS. GUIDANCE FOR HOME CARE CAN COME FROM DIFFERENT SERVICES IN THE CARE NETWORK. THE PROVISION OF CARE IS THE RESPONSIBILITY OF A MULTIDISCIPLINARY HOME CARE TEAM (EMAD) AND A MULTIDISCIPLINARY SUPPORT TEAM (EMAP), SHARING RESPONSIBILITY WITH FAMILY MEMBERS AND/OR DESIGNATED CAREGIVERS. ITS MAIN GOAL IS TO PROVIDE PHYSICAL, EMOTIONAL AND SOCIAL ASSISTANCE TO ELDERLY PEOPLE WHO NEED HELP CARRYING OUT DAILY ACTIVITIES AND MAINTAINING A PROPER QUALITY OF LIFE. THE PROJECT WAS CARRIED OUT IN THE FORM OF THERAPEUTIC GROUPS, AT THE HOME CARE CENTER (SAD), AT PRAA CURUMIM AND AT UNIEVANGLICA, IN THE TOWN OF CERES - GO. THE GROUPS WERE HELD FROM APRIL TO SEPTEMBER 2023, COVERING A DIFFERENT THEME EACH MONTH, LED BY STUDENTS FROM THE MULTIDISCIPLINARY LEAGUE OF CERES (LAMUC). THUS, THE FOLLOWING THEMES WERE EXPLORED: EMOTIONAL CARE, FIRST AID, DECUBITUS CHANGE AND CARING FOR CAREGIVERS - INDUCED RELAXATION. THEREFORE, A SURVEY WAS CARRIED OUT WITH NINE OBJECTIVE QUESTIONS TO ANALYZE THE PROFILE OF THE CAREGIVERS WHO TAKE PART IN THIS PROGRAM, A TOTAL OF 33 PATIENTS WITH DIFFERENT PATHOLOGIES. HOWEVER, A SAMPLE OF N=10 PARTICIPANTS WAS COLLECTED. THE FINAL RESULT WAS AS FOLLOWS: 30% ARE HIRED CAREGIVERS, 50% FAMILY AND 20% BOTH; 100% FEMALE; 10% BETWEEN 26-40 YEARS OLD, 30% FROM 42-55 YEARS OLD, 60% OVER 55 YEARS OLD; 60% ARE IN A CONSCIOUS MENTAL STATE, WHILE 40%, UNCONSCIOUS; 50% MAKE USE OF A GTT TUBE, 40% ORAL FEEDING (SOLID AND LIQUID) AND 10% ONLY LIQUIDS; 20% USE RESPIRATORY SUPPORT FULL TIME, 20% DON’T AND 10% USE IT OCCASIONALLY; 60% CAN COMMUNICATE VERBALLY, 20% COMMUNICATE NON-VERBALLY (WITH GESTURES AND BLINKS) AND 20% DON’T COMMUNICATE; 70% SAID THEY HAVE DIFFICULTY CHANGING THEIR POSITION AND 30% DON’T. 90% HAD DIFFICULTY DRESSING AND DRESSING; 90% HAD DIFFICULTY BANDAGING AND 10% DID NOT. NEVERTHELESS, IT WAS POSSIBLE TO NOTICE THAT FEMALE FAMILY CAREGIVERS, AGED OVER 55, CARING FOR PATIENTS IN A CONSCIOUS STATE OF MIND, WHO USE A GTT TUBE, WHO DON’T NEED BREATHING SUPPORT, WHO COMMUNICATE VERBALLY, AND THOSE WHO HAVE DIFFICULTY CHANGING THEIR POSITION AND BANDAGING THEIR WOUNDS, WERE THE ONES WHO PREVAILED.